Estimation of IDF Curves of Extreme Rainfall by Simple Scaling in Northern Oueme Valley, Benin Republic (West Africa) (2016)
Rainfall intensity-duration-frequency (IDF) curves are of particular importance in water resources management, for example, in urban hydrology, for the design of hydraulic structures and the estimation of the flash flood risk in small catchments. IDF curves describe rainfall intensity as a function of duration and return period, and they are significant for water resources planning, as well as for the design of hydraulic constructions and structures. In this study, scaling properties of extreme rainfall are examined to establish the scaling behavior of statistical non-central moment over different durations. IDF curves and equations are set up for all stations by using the parameter obtained from scaling behavior, the location and scale parameters μ24 and σ24 of the Gumbel distribution (EVI) sample of annual maximum 1440 min rainfall data. In another hand, we have established the IDF curves for ten selected rain gauge stations in the Northern (Oueme Valley) parts of Benin Republic, West Africa by using the simple scaling approach. Analysis of rainfall intensities (5 min and 1440 min rainfall data) from the ten rainfall stations shows that rainfall in north-Benin displays scales invariance property from 5 min to 1440 min. For time scaling, the statistical properties of rainfall follow the hypothesis of simple scaling. Therefore, the simple scaling model applies to the rainfall in (Oueme Valley). Hence, the simple scaling model is thought to be a viable approach to estimate IDF curves of hourly and sub-hourly rainfall form rainfall projections. The obtained scaling exponents are less than 1 and range from 0.23 to 0.59. The empirical model shows that the scaling procedure is a good estimator as it is more efficient and gives more accurate estimates compared with the observed rainfall than the traditional method which only consists the Gumbel model in all stations for lower return periods (T5 years) but not for higher return periods. Estimación de las Curvas IDF de Extrema Precipitación por Escala Simple en el Valle Oueme, al Norte de la República de Benín (Africa occidental) ResumenLas curvas de precipitación Intensidad-Duración-Frecuencia (IDF) son de particular importancia en el manejo de los recursos hídricos, como es el caso de la hidrología urbana o para el diseño de estructuras hidráulicas y la estimación del riesgo de crecidas en pequeñas captaciones. Las curvas IDF describen la intensidad de las precipitaciones como una función con períodos de duración y recurrencia, lo que las hace significativas en la planeación de recursos hídricos así como en el diseño de construcciones y estructuras hidráulicas. Este estudio examina las propiedades de escala en precipitaciones extremas para establecer un comportamiento en momentos estadísticos marginales en diferentes períodos de duración. Se establecieron las curvas IDF y las ecuaciones para todas las estaciones a partir del parámetro obtenido del comportamiento de escala, la ubicación y los parámetros de escala μ24 and σ24 de la muestra de información de precipitación máxima anual de 1440 minutos de la distribución de Gumbel (EVI). Por otro lado, se establecieron las curvas IDF para 10 estaciones pluviométricas seleccionadas en el Valle Oueme, al norte de la República de Benín (África occidental), con el uso de aproximación simple de escala. El análisis de las intensidades de precipitación en las diez estaciones pluviométricas muestra que la precipitación en el norte de Benín expone propiedades de poca variación en la escala 5 min y 1440. En el tiempo de escala, las propiedades estadísticas de precipitación confirman la hipótesis de escala simple; además, este modelo so corresponde a la precipitación del Valle Oueme. Por lo tanto, el modelo de escala simple se considera una aproximación viable para estimar las curvas IDF en las proyecciones de precipitación de cada hora y sub-hora. Los exponentes de escala obtenidos son menores a 1 y oscilan de 0,23 a 0,59. El modelo empírico muestra que el procedimiento de escala es un buen estimativo, más eficiente y con cálculos más exactos que el método tradicional, el cual consiste solamente en el modelo Gumbel aplicado en todas las estaciones pluviométricas en períodos de menor recurrencia (T5 años) pero no en lapsos de mayor recurrencia.